Sepsis, Endocarditis, and Purulent Arthritis due to a Rare Zoonotic Infection with Streptococcus equi Subspecies zooepidemicus - Anne Kirstine Høyer-Nielsen; Shahin Gaini; Anne Kjerulf; Rudi Kollslíð; Torkil Á Steig; Marc Stegger; Jan Jóanesarson (Case Reports in Infectious Diseases)
Streptococcus equi subspecies zooepidemicus (S. zooepidemicus) is mostly known as an opportunistic pathogen found in horses and as a rare human zoonosis. An 82-year-old male, who had daily contact with horses, was admitted in a septic condition. The patient presented with dyspnea, hemoptysis, impaired general condition, and severe pain in a swollen left shoulder. Synovial fluid from the affected joint and blood cultures showed growth of S. equi subsp. zooepidemicus. Transesophageal echocardiography showed a vegetation on the aortic valve consistent with endocarditis. Arthroscopic revision revealed synovitis and erosion of the rotator cuff. Technetium-99m scintigraphy showed intense increased activity in the left shoulder, suspicious of osteitis. The infection was treated with intravenous antibiotics over a period of five weeks, followed by oral antibiotics for another two months. The patient recovered without permanent sequelae.